2015
DOI: 10.1111/1462-2920.13018
|View full text |Cite
|
Sign up to set email alerts
|

CmpacC regulates mycoparasitism, oxalate degradation and antifungal activity in the mycoparasitic fungus Coniothyrium minitans

Abstract: The PacC/Rim101 pH-responsive transcription factor is an important pathogenicity element for many plant-pathogenic fungi. In this study, we investigated the roles of a PacC homologue, CmpacC, in the mycoparasitic fungus Coniothyrium minitans. CmpacC was confirmed to have the transcriptional activation activity by the transcriptional activation test in Saccharomyces cerevisiae. Disruption of CmpacC resulted in impaired fungal responses to ambient pH. Compared to the wild-type, the CmpacC-disruption mutant ΔCmpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 48 publications
0
38
1
Order By: Relevance
“…C. minitans is able to grow under a wide range of ambient pH conditions, and recent studies showed that C. minitans can adjust ambient pH via the PacC system to coordinate antibiosis and parasitism. Under low pH conditions, C. minitans produces antifungal substances, while with increased ambient pH, C. minitans secretes fungal cell wall degrading enzymes (Zeng et al ., 2014; Lou et al ., ). It is likely that CmVps39 is involved in the parasitism via the PacC system, and at least partially dependent on the PacC system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. minitans is able to grow under a wide range of ambient pH conditions, and recent studies showed that C. minitans can adjust ambient pH via the PacC system to coordinate antibiosis and parasitism. Under low pH conditions, C. minitans produces antifungal substances, while with increased ambient pH, C. minitans secretes fungal cell wall degrading enzymes (Zeng et al ., 2014; Lou et al ., ). It is likely that CmVps39 is involved in the parasitism via the PacC system, and at least partially dependent on the PacC system.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression of Cmg1 increased in presence of the ground sclerotia of S. sclerotiorum and during parasitic interaction with S. sclerotiorum , indicating that β‐1,3‐glucanase may play important roles in the parasitic process (Giczey et al ., ). Recent research revealed that degradation of oxalic acid, an essential pathogenicity factor of S. sclerotiorum , regulated mycoparasitism and antibiosis of C. minitans against S. sclerotiorum , in which a zinc finger transcription factor pacC homologue, CmPacC, plays an important regulating role (Zeng et al ., ; Lou et al ., ). The parasitism of C. minitans is likely very complicated, and shares some signal transduction pathways with conidiation (Muthumeenakshi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Representative isolates of different resistant phenotypes and Colletotrichum species were selected for sequencing of their β-tubulin 2 (TUB2) genes. The mycelia of Colletotrichum isolates were obtained by using a previously published protocol (Lou et al 2015). The mycelia of each isolate were ground to a fine powder in liquid nitrogen with a mortar and pestle.…”
Section: Sequence Analysis Of β-Tubulin 2 Genesmentioning
confidence: 99%
“…PacC has been shown to regulate fungal virulence towards mammalian, plant, insect and fungal hosts (Cornet and Gaillardin, ; Rollins, ; Kim et al, ; Alkan et al, , ; Landraud et al, ; Zhang et al, ; Huang et al ., 2015; Lou et al, ). In most cases, the absence or reduced production of PacC leads to a partial to total absence of pathogenicity, but increased virulence has also been reported in Fusarium species (Caracuel et al, ; Merhej et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, numerous studies have confirmed that this pH signalling pathway is specific and conserved throughout the fungal kingdom. The construction and study of PacC/Rim101 deletion strains in multiple fungal species have revealed that this regulator is required for virulence in human, insect, fungus and plant pathogens (for review, see Alkan et al, ; Landraud et al, ; Bertuzzi et al, ; Cornet and Gaillardin, ; Huang et al ., ; Ost et al, ; Lou et al, ; Luo et al, ). In most cases, PacC plays a role in enzyme and metabolite production and/or fungal cell wall remodelling that are required in the infectious process.…”
Section: Introductionmentioning
confidence: 99%